ANALYZING AND COMPARING ANTHROPOMETRIC INDICES AS CONTRIBUTORY FACTORS OF INFLUENCE IN SPORTS PERFORMANCE - Dan Alexandru SZABO; Nicolae NEAGU; Alexandra Camelia GLIGA; Ioan Sabin SOPA (Editura Universităţii din Oradea, 2020)
Sports anthropometry techniques and procedures have been developed over numerous studies and applied in research related to physical or biological anthropology. The purpose of our study was to provide some individual reference anthropometric values in terms of body height and weight, age, the highest points reached by the use of both hands in attack and block actions. The provided data will give us a general overview of the players' anthropometric characteristics regarding their court position. Furthermore, the team position specialization also requires some other biomechanical and dynamic indices of female volleyball players. Values found for height, body weight, and body mass index (BMI) showed similar trends and different characteristics depending on each player's specialization. Our research was conducted in the "Anton Pongratz" Sports Hall within the University of Medicine, Pharmacy, Science, and Technology (UMFST) of Târgu Mureş, for the applied part, and the Department of Human Movement Sciences, for the part of the theoretical foundation of our study. We had a sample group of 12 subjects, all high-performance sports players from the National University Centre of Excellence in Volleyball (NUCEV) - for female teams as an institutional part of the University Sports Club (USC) of UMFST Târgu Mureş. We reported the results of our subjects to a large sample, including 1459 female players who have participated in seven editions of World Championship and Olympic Games between 2000 and 2012. Players' data information was obtained from several different competition databases posted on the International Volleyball Federation (FIVB) official website (www.fivb.org) and from more specialized published papers (i.e. ISI or BDI journals) dealing with this topic. As a result of our study, we can emphasize that we have found a positive correlation between Height to Spike reach and block reach (r = 0.6531, p <0.05 / r = 0.6170, p <0.05), spike reach and block reach (r = 0.5883, r2 = 0.3461, p <0.05 / r = 0.6044, r2 = 0.3653, p <0.05) r = 0.4565, r2 = 0.2083, p> 0.05 / r = 0.4759, r2 = 0.1178, p> 0.05).